Mobile phone usage, sleep quality, and life satisfaction among university students in Malaysia - Abdullah, Haslinda; Marzuki, Nurul Fatehah; Ma’rof, Aini Azeqa; Md Sham, Fariza (Human Resource Management Academic Research Society, 2022)
Life satisfaction is a cognitive evaluation on one’s life, ranging from positive to negative. This study aims to determine the relationship between mobile phone usage, sleep quality, and life satisfaction among university students in Malaysia. Sample of this study was 463 university students from National University of Malaysia (UKM) and University Putra Malaysia (UPM), age between 18-30 years old. Sample was chosen using snowball technique. Instruments used for this study are Satisfaction with Life Scale (SWLS), Test of Mobile Phone Dependence (TMD), and Cleveland Adolescence Sleep Questionnaire (CASQ). Data was collected using an online self-administered survey questionnaire. Statistical Package for Social Sciences (SPSS) was used to analyse the data. Pearson correlation was used to describe relationships between the three variables. In determining the predictor of life satisfaction, multiple regression was conducted to determine which factors contribute most to life satisfaction among university students The result shows that mobile phone usage contributed positively amounting to 21.3% of students’ quality of life (? = .213; p <.05) and sleep quality contributed negatively to 36.9% of students' quality of life (? = -.369; p <.05). Majority of university students, who participated in this study are having an average level of satisfaction with life. These results showed that, being a young adult and university students at the same time, decreases their perception on how they feel and evaluate on life satisfaction.